2009
DOI: 10.1074/jbc.m808128200
|View full text |Cite
|
Sign up to set email alerts
|

Slc2a5 (Glut5) Is Essential for the Absorption of Fructose in the Intestine and Generation of Fructose-induced Hypertension

Abstract: The identity of the transporter responsible for fructose absorption in the intestine in vivo and its potential role in fructose-induced hypertension remain speculative. Here we demonstrate that Glut5 (Slc2a5) deletion reduced fructose absorption by ϳ75% in the jejunum and decreased the concentration of serum fructose by ϳ90% relative to wild-type mice on increased dietary fructose. When fed a control (60% starch) diet, Glut5 ؊/؊ mice had normal blood pressure and displayed normal weight gain. However, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
193
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(209 citation statements)
references
References 40 publications
11
193
1
1
Order By: Relevance
“…The presence of apical GLUT2 should enable fructose absorption when GLUT5 activity is limiting; however, GLUT5 knockout mice cannot absorb fructose, even when their intestine is infused with high concentrations of glucose or fructose (33) . In addition, immunohistochemistry using two different antibodies raised against peptides corresponding to the C-terminal region, or to residues 40-55 of the GLUT2 amino acid sequence has demonstrated that the GLUT2 protein is exclusively located on the basolateral membrane of enterocytes (23)(24)(25) .…”
Section: Intestinal Glucose Transportmentioning
confidence: 99%
“…The presence of apical GLUT2 should enable fructose absorption when GLUT5 activity is limiting; however, GLUT5 knockout mice cannot absorb fructose, even when their intestine is infused with high concentrations of glucose or fructose (33) . In addition, immunohistochemistry using two different antibodies raised against peptides corresponding to the C-terminal region, or to residues 40-55 of the GLUT2 amino acid sequence has demonstrated that the GLUT2 protein is exclusively located on the basolateral membrane of enterocytes (23)(24)(25) .…”
Section: Intestinal Glucose Transportmentioning
confidence: 99%
“…11,12 Recent human data from infant 13,14 and diabetic 15 studies have supported this, where a reduced expression of GLUT5 were associated with high rates of fructose malabsorption. Moreover, fructose malabsorption is not associated with GLUT2 or GLUT5 mutations.…”
mentioning
confidence: 73%
“…The importance of GLUT5 in fructose absorption has been investigated further in a GLUT5 knockout mouse model (2). In these GLUT5 knockout mice fructose absorption was decreased by 75% in the jejunum and the concentration of serum fructose was decreased by 90%, compared with wild-type mice.…”
Section: Transport Of Fructosementioning
confidence: 99%
“…Recently, a GLUT5 knockout mouse model was shown to exhibit decreased absorption of dietary fructose, with consequent distension of the large intestine with fluid and gas. The model was described as having the hallmarks of profound fructose malabsorption (2). With this and other advances in the understanding of fructose transport, it may become possible to characterize a mechanism for fructose malabsorption in humans.…”
mentioning
confidence: 99%